Functional attributes of epilithic diatoms for palaeoenvironmental interpretations in South-West Greenland lakes - McGowan, Suzanne; Gunn, Hazel V.; Whiteford, Erika J.; Anderson, N. John; Jones, Vivienne J.; Law, Antonia C. (Springer, 2017)
Benthic diatoms are commonly used for palaeoenvironmental reconstruction in Arctic regions, but interpretation of their ecology remains challenging. We studied epilithic diatom assemblages from the shallow margins of 19 lakes from three areas (coast-inland-ice sheet margin) along a climate gradient in Kangerlussuaq, West Greenland during two periods; shortly after ice-off (spring) and in the middle of the growth season (summer). We aimed to understand the distribution of Arctic epilithic diatoms in relation to water chemistry gradients during the two seasons, to investigate their incorporation into lake sediments and to assess their applicability as palaeoenvironmental indicators. Diatoms were correlated with nutrients in the spring and alkalinity/major ions in the summer, when nutrients were depleted; approximately half of the variance explained was independent of spatial factors. When categorised by functional attributes, diatom seasonal succession differed among regions with the most obvious changes in inland lakes where summer temperatures are warmer, organic nutrient processing is prevalent and silicate is limiting. These conditions led to small, motile and adnate diatoms being abundant in inland lakes during the summer (Nitzschia spp., Encyonopsis microcephala), as these functional attributes are suited to living within complex mats of non-siliceous microbial biofilms. Seasonal succession in silica-rich lakes at the coast was less pronounced and assemblages included Tabellaria flocculosa (indicating more acidic conditions) and Hannaea arcus (indicating input from inflowing rivers). The nitrogen-fixing diatom Epithemia sorex increased from the coast to the ice sheet, negatively correlating with a gradient of reactive nitrogen. The presence of this diatom in Holocene sediment records alongside cyanobacterial carotenoids during arid periods of low nitrogen delivery, suggests that it is a useful indicator of nitrogen limitation. Nitzschia species appear to be associated with high concentrations of organic carbon and heterotrophy, but their poor representation in West Greenland lake sediments due to taphonomic processes limits their palaeoenvironmental application in this region. Proportions of epilithic taxa in lake sediment records of coastal lakes increased during some wetter periods of the Holocene, suggesting that snowpack-derived nutrient delivery may offer diatom taxa living at lake margins a competitive advantage over planktonic diatoms during the “moating” ice melt period. Thus, further research investigating linkages between epilithic diatoms, snowpack and nutrient delivery in seasonally frozen lakes is recommended as these taxa live on the ‘front-line’ during the spring and may be especially sensitive to changes in snowmelt conditions.